INSTRUIREA PROFESIONALĂ A BIBLIOTECARILOR CA FACTOR DE DEZVOLTARE A ABILITĂŢILOR CREATIVE - IFTODI, magistru în ştiinţe ale comunicării, Lina (BIBLIOPOLIS, 2020)
An efficient management presupposes the taking into account of all objective and subjective moments that lead to the development of creative skills of the staff. Through this article the author presents efficiency of training process in ML, outlines creativity of librarians and its influence on present development and for the future. Also, the article outlines the effects of the training process in development of creative abilities of librarians as being innovational element in realization of performances of ML. Librarian’s views were taken from research that was made by the author within the program Management of infodocumentary institution, to obtain a master’s degree in communication sciences. The results of research can be useful for managers in mapping projects in improvement of process of training and professional development, revaluation of librarian’s creative potential, because they represent creative element, active and coordinating of the whole library’s creativity.